A diagrammatic approach of impedimetric phase angle-modulus sensing for identification and quantification of various polar and non-polar/ionic adulterants in milk. (January 2021) - Das, Chirantan; Chowdhury, Basudev Nag; Chakraborty, Subhadip; Sikdar, Subhrajit; Saha, Rajib; Mukherjee, Anuraag; Karmakar, Anupam; Chattopadhyay, Sanatan
Abstract: The current article demonstrates a novel diagrammatic approach for the detection and quantification of polar and non-polar/ionic adulterants in milk by employing electrical impedance spectroscopy (EIS). For such study, some commonly used milk adulterants including melamine, starch, urea, allantoin, cyanuric acid, benzoic acid, ammonium sulphate and sodium bicarbonate are incorporated in a controlled manner in the pure milk sample. The presence of such adulterants in milk is confirmed by Fourier transform mid-infrared (FT-MIR) spectroscopy prior to impedimetric measurements. A Pt/Teflon/SiO2/Si biosensor device is fabricated for EIS measurement where the combination of SiO2 and Teflon layer thicknesses are optimized to obtain an appropriate hydrophobicity/dielectricity for the liquid milk samples. The EIS study shows an opposite trend in the variation of electrical impedance, capacitance and conductance for the polar samples in comparison to non-polar/ionic adulterants, upon their controlled addition from 0.5 to 9 (mg/g). Such results are utilized for detection and quantification of the milk-adulterants by developing a diagrammatic approach based on impedimetric phase angle-modulus mapping. Such diagrammatic impedance spectroscopy provides a generic scheme for a rapid, cost-effective and point-of-care detection and quantification of adulterants in milk which can be further extended to other bio-consumables. Highlights: EIS detection scheme to identify polar and non-polar/ionic adulterants in milk. Pt/teflon/SiO2/Si biosensor device fabricated for EIS measurement of liquid sample. The device can detect milk adulterant concentration ranging from 0.05 to 0.9% (w/w). Impedimetric phase angle-modulus diagram can map various adulterants in milk.